A High‐Index Ge2Sb2Te5‐Based Fabry–Perot Cavity and Its Application for Third‐Harmonic Generation. Issue 7 (19th June 2019) - Cao, Tun; Liu, Kuan; Tang, Yutao; Deng, Junhong; Li, Kingfai; Li, Guixin
Abstract: Third‐order harmonic generation (THG) plays a vital role in microscopy, optical communications, etc. Conventional methods of obtaining efficient THG in macroscopic crystals is already mature; however, they will finally limit the miniaturization and integration of on‐chip laser sources. To date, THG from either photonic crystals or metamaterials provides compact photonic platforms; however, selection of materials remains elusive. Herein, a giant enhancement of THG efficiency from an air/high index Ge2 Sb2 Te5 (GST)/gold multi‐layered Fabry–Perot cavity is experimentally demonstrated. At cavity resonant wavelength in near‐infrared regime, the efficiency of THG from a 50‐nm thick amorphous GST planar film is boosted 422 times compared to that of nonresonant conditions. Interestingly, the THG efficiency has a dramatic decrease of three orders when the structural state of GST is transformed from amorphous to crystalline. These findings have a potential for achieving an ultracompact nonlinear optical source with high efficiency and switchable functionality. Abstract : A giant enhancement of third‐harmonic generation (THG) efficiency from an air/Ge2 Sb2 Te5 (GST)/gold multi‐layered Fabry–Perot cavity is presented. Interestingly, the THG efficiency has a dramatic decrease of three orders when the structural state of GST transforms from amorphous to crystalline. These findings have a potential for achieving an ultracompact nonlinear optical source with high efficiency and switchable functionality.